Diagnostic and statistical manual of mental disorders DSM-5-TR (American Psychiatric Association Publishing, 2022)
The Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, Text Revision (DSM-5-TR), is the most comprehensive, current, and critical resource for clinical practice available to today's mental health clinicians and researchers. DSM-5-TR includes fully revised text and references, updated diagnostic criteria and ICD-10-CM codes since DSM-5 was published in 2013. It features a new disorder, prolonged grief disorder, as well as codes for suicidal behavior available to all clinicians of any discipline without the requirement of any other diagnosis. With contributions from over 200 subject matter experts, this updated volume boasts the most current text updates based on the scientific literature. Now in four-color and with the ability to authenticate each printed copy, DSM-5-TR provides a cohesive, updated presentation of criteria, diagnostic codes, and text. This latest volume offers a common language for clinicians involved in the diagnosis and study of mental disorders and facilitates an objective assessment of symptom presentations across a variety of clinical settings-inpatient, outpatient, partial hospital, consultation-liaison, clinical, private practice, and primary care. Important updates in DSM-5-TR include 1) fully revised text for each disorder with updated sections on associated features, prevalence, development and course, risk and prognostic factors, culture, diagnostic markers, suicide, differential diagnosis, and more; 2) addition of prolonged grief disorder (PGD) to Section II; 3) over 70 modified criteria sets with helpful clarifications since publication of DSM-5; 4) fully updated Introduction and Use of the Manual to guide usage and provide context for important terminology; 5) considerations of the impact of racism and discrimination on mental disorders integrated into the text; 6) new codes to flag and monitor suicidal behavior, available to all clinicians of any discipline and without the requirement of any other diagnosis; 7) fully updated ICD-10-CM codes implemented since 2013, including over 50 coding updates new to DSM-5-TR for substance intoxication and withdrawal and other disorders.